Сильноточный бетатрон и двухкамерный стереобетатрон: проспект - Скворцов Ю. М.; Шестаков В. Г.; Окулов Б. В.; Гончаров В. Я.; Слупский А. М.; Москалев В. А. Владилен Александрович (Томск, 1966)
В фонде НТБ ТПУ отсутствует